The Occurrence of Meniscal and Chondral Injury in Two-Stage Revision Anterior Cruciate Ligament Reconstruction: A Consecutive Case Series - van Tol, Floris R.; Kernkamp, Willem A.; van der Wal, Robert J. P.; Swen, Jan-Willem A.; Van de Velde, Samuel K.; van Arkel, Ewoud R. A. (The Journal of Knee Surgery, 2020)
Two-stage revision anterior cruciate ligament (ACL) reconstruction is an effective way to revise suboptimal tunnel-placement allowing for proper graft fixation. However, prolonged increased laxity of the knee may increase the risk of meniscal or chondral injury. It was hypothesized that no additional meniscal or chondral lesions occur in between the two stages of the two-stage revision ACL reconstruction. In this retrospective study, 42 patients undergoing a two-stage revision ACL reconstruction were included. Surgical notes for both stages were screened for meniscal and chondral status, interventions to any concurrent injury, surgery dates, along with basic patient characteristics. In 4 of the 42 patients, a new meniscal tear occurred in between the two stages, of which three required partial meniscectomy during the second stage of the ACL revision. One patient experienced a new small degenerative tear that did not require intervention. Two out of the four menisci that were repaired during the first stage had failed and required partial meniscectomy. No significant difference was found in the time between the two stages with respect to the occurrence of meniscal tears. No significant differences in chondral status were found. In conclusion, approximately 10% of patients developed a new meniscal tear and no difference in macroscopic chondral injury was observed between the first and second stages.
Keywords: revision anterior cruciate ligament reconstruction; meniscal tears; two-stage revision; bone grafting